Hybrid Learning Development to Improve Teacher Learning Management - Disa Hediansah; Herman Dwi Surjono (JKTP: Jurnal Kajian Teknologi Pendidikan, 2020)
Abstract: Teacher learning management is an important part of achieving the process and results within the scope of education. In addition, the development towards technology optimization is called era 4.0 as globalization which is part of the sustainability of innovation in 21st Century Education. Therefore this study aims to develop and investigate hybrid learning methods for teacher learning management. This research and development has passed the feasibility validity test with a score of 78.5 in the good category by media experts and 105.5 in the excellent category by material experts. This study involved 41 of them 9 teachers and 32 students at the Community Learning Center (PKBM Package-C) in Ciamis District. The outcame showed a positive response to teacher learning management with a score of 91 in the Very good category. The result show that the effect by hybrid learning has had an impact interactive environment and can learn to be independent (for upgrade them skill) including interaction with teacher or peers. Limitation and future research are discussed.